Implementasi Fungsi Pendidikan Politik Oleh Partai Demokrasi Indonesia Perjuangan Di Kabupaten Purworejo Menurut Undang-Undang Nomor 2 Tahun 2011 Tentang Perubahan Atas Undang-Undang Nomor 2 Tahun 2008 Tentang Partai Partai Politik - Recalliandra Marella Zainenci; Sunny Ummul Firdaus; Jadmiko Anom Husodo (Aktivisme: Jurnal Ilmu Pendidikan, Politik dan Sosial Indonesia, 2024)
A political party is an institution that is necessary in the democratic world; if you have chosen a democratic system to regulate the life of the nation and state, one of the essential instruments in democracy is the institution of political parties. Political education is a significant activity in a nation based on democracy because democracy and the democratization process require absolute conditions for political public education; how the function of political education by the Indonesian Democratic Party of Struggle in Purworejo Regency is by Law Number 2 of 2011 concerning Amendments to Law Number 2 of 2008 concerning Political Parties. This study aims to analyze the implementation of norms related to the function of political education by DPC PDI Perjuangan in Purworejo Regency. This research uses an empirical approach. This study uses a qualitative descriptive analysis method with a case approach. The data used in this study are primary data obtained directly by researchers in the field through respondents through observation, interviews, and questionnaire distribution, as well as secondary data, namely data obtained or obtained from information or knowledge obtained indirectly, including official documents, books, and research results in the form of reports. The data collection techniques used in this study are field studies and literature studies. The result of this study is that there are seven political education activities carried out by PDI Perjuangan Purworejo Regency, namely, political education through socialization, political education through social, political education through art and culture, political education through religion, political education through party wing organizations, political education through seminars, political education through party schools.